Paleonutrition - Hockett, Bryan (Ethnobiology Letters, 2011)
Review of Paleonutrition. Mark Q. Sutton, Kristin D. Sobolik, and Jill Gardner. 2010. University of Arizona Press, Tucson. Pp. 384, black‐and-white illustrations. 75.00 (hardback). ISBN 9780816527946.